Analisis Kesalahan Morfologis Pada Karangan DeskripsiSiswa Kelas Vii SMP Negeri 1 Kradenan Tahun Ajaran 2015/2016 - Oktaviani, Ella Sari, Drs. Yakub Nasucha, M.Hum (2016)
This study aims to 1) to describe the morphology of form errors on the text description of the student, 2) to determine the level of process errors morphological description text students. Type peneltian qualitative. The object of research in the form of manifestation of morphological mistakes and errors in the text morphological description graders. Data were collected through technical log and see, plus the method of documentation. Data were analyzed using advanced engineering techniques Shared with dressing and insertion techniques. The results of this study 1) related to the morphological form of error found two errors that a) affixation (prefix writing was separated from the base, refining his prefixes, prefixes disappearances happened, the removal of prefixes ber-, writing prefix ke- separated from said base, combined writing and -kan -i suffix, the suffix -an omission, writing his suffix separated from the base, an air-removal konfiks, writing an konfiks all) b) reduplication (repetition part, loops with variations phoneme and re-writing of the word) and 2) related to the level of morphological errors found an error that is highest on the error prefix in as many as nine errors. The cause of the error rate prefixes be separated from the base of the most dominant in the morphological because of some things that students have not mastered the material on the formation of words and the students have not been able to distinguish between prefixes and prefix in-. The conclusions of this study are students of SMP Negeri 1 Kradenan in the use of morphological still many errors in an essay. Errors triggered by a lack of understanding of the material forming the word by the students. Keywords: affixation, morphological errors, reduplication, text description.